Л. А. Нагорная. Ленинские уроки правды - Зубалій, О.Д.; Траф'як, М.В. (Український історичний журнал, 1990)
Рецензія на видання: Л. А. Нагорная. Ленинские уроки правды. К.: Политиздат Украиньї, 1989.—208 с.